Atypical food packaging affects the persuasive impact of product claims. (March 2016) - van Ooijen, Iris; Fransen, Marieke L.; Verlegh, Peeter W.J.; Smit, Edith G.
Highlights: In an experiment, we asked participants to evaluate a food product in a web shop. Packaging typicality and product claim strength were manipulated between subjects. Atypicality enhanced the impact of strong claims on quality perception. Atypicality also enhanced the negative impact of weak claims on willingness to pay. Increased processing, caused by atypical packaging, mediated these effects. Abstract: Atypical food packaging draws attention in the retail environment, and therefore increases product salience. However, until now, no research has focused on how atypical packaging affects the persuasive impact of other food information. In the present study, we propose that atypical packaging enhances processing of product information, affecting product claim recall and product evaluation in turn. Specifically, we argue that atypical packaging may have detrimental consequences for the evaluation of food products that are presented with so-called weak product claims. Participants ( N  = 102) were presented with an online shopping environment, showing a food product with either a typical or an atypical package, and product claims that were either weak or strong. Results showed that atypical shaped packaging design enhanced cognitive processing, which in turn decreased the persuasive impact of weak claims on willingness to pay, and increased the persuasive impact of strong product claims on quality judgment. Furthermore, product knowledge improved when packaging design was atypical, through increased processing.